2017
DOI: 10.1371/journal.pone.0174142
|View full text |Cite
|
Sign up to set email alerts
|

Coding and non-coding gene regulatory networks underlie the immune response in liver cirrhosis

Abstract: Liver cirrhosis is recognized as being the consequence of immune-mediated hepatocyte damage and repair processes. However, the regulation of these immune responses underlying liver cirrhosis has not been elucidated. In this study, we used GEO datasets and bioinformatics methods to established coding and non-coding gene regulatory networks including transcription factor-/lncRNA-microRNA-mRNA, and competing endogenous RNA interaction networks. Our results identified 2224 mRNAs, 70 lncRNAs and 46 microRNAs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, this competing mechanism also affects immune responses, such as in liver cirrhosis [ 164 ] or in early HIV infection (EHI) gene expression regulatory networks [ 165 ] and it participates in the regulation and evolution of deceitful autoimmune diseases like rheumatoid arthritis [ 166 , 167 ].…”
Section: Cerna and Diseasesmentioning
confidence: 99%
“…Interestingly, this competing mechanism also affects immune responses, such as in liver cirrhosis [ 164 ] or in early HIV infection (EHI) gene expression regulatory networks [ 165 ] and it participates in the regulation and evolution of deceitful autoimmune diseases like rheumatoid arthritis [ 166 , 167 ].…”
Section: Cerna and Diseasesmentioning
confidence: 99%
“…Other causes include primary biliary cirrhosis (PBC), autoimmune hepatitis, primary sclerosing cholangitis, and genetic and metabolic diseases, such as Wilson's disease and hemochromatosis. A complex gene regulatory network underlying immune response processes might play an important role in the development and progression of liver cirrhosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 33 found that miR-219-5p prevented cirrhosis through increasing keratinocyte growth factor (KGF). The study by Gao et al 34 indicated that miR-219-5p was differentially expressed in liver cirrhosis, suggesting that miR-219-5p might affect the process of liver cirrhosis. The above evidence indicated the important role of miR-219-5p in liver injury.…”
Section: Discussionmentioning
confidence: 99%